Dividend Yield and Price-Earnings Ratio: A Further Look - Imam, Shahed (The International Journal of Accounting and Business Society, 2004)
The dividend Yield and Price Earnings Ratio are two widely used measures of share valuation. This paper presents the value relevance controversy of these two measures. It reveals that both D/Y and P/E provide useful information to rational investors but D/Y can vary independently of the value of the company and P/E ratio is also uninformative. Keywords: Earnings, lnfomation, Dividend, Valuation, Growth, Uncertainty.